(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the feasibility and early outcomes of subxiphoid uniportal video-assisted thoracoscopic surgery (VATS) for thymectomy in the treatment of myasthenia gravis and thymic tumors at Bach Mai Hospital. Materials and Methods: A prospective case series study was conducted on patients indicated for subxiphoid uniportal VATS thymectomy at the Department of Thoracic Surgery, Bach Mai Hospital, from December 2024 to November 2025. Clinical indicators, histopathological characteristics, and early postoperative results were collected and analyzed. Results: From December 2024 to November 2025, 39 patients (29 females and 10 males) underwent subxiphoid uniportal video-assisted thoracoscopic surgery thymectomy at Bach Mai Hospital. The mean age was 51.2 ± 13.1 years; 34 patients had myasthenia gravis (87.2%). The mean tumor size was 2.9 ± 1.2 cm. Histopathological results showed 7 cases of thymic hyperplasia (17.9%), 4 cases of benign thymic cysts (9.8%), and 28 cases of thymoma (71.8%), including: 2 cases of type A (7.1%), 9 cases of type AB (32.1%), 2 cases of type B1 (7.1%), 11 cases of type B2 (39.3%), and 4 cases of type B3 (14.3%). The mean operative time was 101.4 ± 23.8 minutes (range: 70–160 minutes). One case of intraoperative innominate vein injury occurred, but no conversion to open surgery was required. The mean chest tube duration was 2.1 ± 0.9 days, and the mean hospital stay was 5.0 ± 4.3 days. No patients experienced phrenic nerve palsy. Postoperative complications included one patient with pneumothorax requiring chest tube re-insertion and two patients with postoperative myasthenic crisis. Conclusions: Subxiphoid uniportal VATS thymectomy is a safe and feasible technique for the treatment of myasthenia gravis and thymic tumors, yielding promising early outcomes at a specialized surgical center.